Pengembangan Aplikasi Penjadwalan Wisata Harian pada Smartphone dengan Pendekatan Scrum - Yen Lina Prasetio; Novita Hanafiah; Agustinna Yosanny; Catharine Yolanda; Febrina Piecella Musbar; Denny Septianto (Bina Nusantara University, 2014)
The technology development affects people activites especially in this 20th century. Mobile phone ischanged into smartphone and travelling becomes a new lifestlye. A Tourism scheduler with a reminder is created from this research to fulfill the new trend of people lifestyle. The travelling data is stored in the system and some information such as the point of interest of an area, hotel, and transportation to reach the area are provided. Waterfall model becomes the method to build this system. Hence, an application that can create a trip for the user is completely built in Blackberry application system, consist of the trip information. The history feature provided in this application can be an advantange for the user to choose the new travelling destination. Moreover, the application has a good interface follow the eight golden rules and has a good performance that helps the tourists/users to create their own schedule and set the reminder for them.